Péptidos de veneno animal y venenos - Novo de Oliveira, Ana (2023)
Venoms are not uncommon biochemical weapons that only a few species possess. It is estimated that 220,000 animal spe cies produce venom, corresponding to approximately 15% of all animal species. Animal venom and poisons can be found in almost all habitats that spiders, scorpions, snakes, amphibians, hymenopteran insects, marine invertebrates, anemones, or jellyfishes inhabit. Animal venom and poisons are species-specific biococktails of dozens or even hundreds of bioactive molecules (Oliveira et al. 2022), which have arisen through positive evolutionary processes that enable animals to improve predation efficiency, to defend and deter competitors